KEANEKARAGAMAN JENIS TUMBUHAN PEMAKAN SERANGGA DAN LAJU FOTOSINTESISNYA DI PULAU NATUNA [Diversity of Insectivorous Plants and Its Photosynthetic Rate in Natuna Island] - Muhammad Mansur (Research Center for Biology-Indonesian Institute of Sciences, 2012)
Studies of insectivorous plants diversity and photosynthesis rate of pitcher plants in Natuna Island was conducted on August 2011, Survey in eleven villages conducted to determine the species found in the visited sites, Bioscientific Portable LCI ADC Photosynthesis System used for measurement of pitcher plants photosynthesic rate, The results shows that there are three families of insectivorous plants founded in study sites, namely Nepenthaceae, Droseraceae and Lentibulariaceae, Six species of Nepenthaceae were found (four species and two natural hybrids) i,e; N. gracilis, N. ampullaria, N. rafflesiana, N. reinwardtiana, N. x hookeriana and N. x trichocarpa. While from family Droseraceae and Lentibulariaceae were found only one species respectively, which is Drosera burmanni and Utricularia bifida. Nepenthes reinwardtiana has the highest rate of photosynthesis namely 21,05 µmol/m /s, followed by N. gracilis (17,66 µmol/m /s), N. rafflesiana (16,6 µmol/m /s), N. x hookeriana (15,84 µmol/m /s) and N. ampullaria (9,96 µmol/m /s).